THE MANY FACES OF ROLE-PLAYING GAME STUDIES - Deterding,S; Zagal,JP (2024)
This chapter provides an introduction to role-playing games and their academic study. It presents role-playing games (RPG) as an intersection of four phenomena: roles, play, games, and media culture. They take a fundamental form of play-make-believe-and a fundamental aspect of social reality and identity-roles-and give them the structured form of a game. Also, they form a central part of contemporary gaming, nerd, and genre media culture. The chapter presents a history of research on role-playing games, an overview of the key concepts discussed in this book, and a guided tour through the Handbook.